Research Cooperation and Research Expenditures with Endogenous Absorptive Capacity: Theory and Microeconometric Evidence for the German Service Sector - Ulrich Kaiser (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
This paper derives a three stage Cournot duopoly game for research collaboration, research expenditures and product market competition. The amount of knowledge firms can absorb from other firms is made dependent on their own research efforts, e.g., firms? absorptive capacity is treated as an endogenous variable. It is shown that cooperating firms invest more in R&D than non?cooperating firms if spillovers are sufficiently large. Further, market demand and R&D productivity have a positive effect on R&D efforts both under research joint venture and under research competition. Firms? propensity to collaborate in R&D is increasing in R&D productivity. The key findings of the theoretical model are tested using German innovation survey data for the service sector. A simultaneous model for cooperation choice and innovation expenditures shows that R&D cooperation has a weakly significant positive effect on innovation expenditures. The empirical results broadly support the theoretical model.
Keywords: O31; C35; 330; research cooperation; research expenditures; knowledge spillovers; simultaneous equation model; services